Adapting to the Instagram Esthetic and Exploring Influencers of Hedonic Consumption. Issue 3 (27th May 2023) - Sood, Abhinav; Quintal, Vanessa; Phau, Ian
Abstract: This paper explores hedonic adaptation and decision-making in hedonic consumption of cosmetic surgery. A mixed-method approach incorporates qualitative research with focus groups and expert panels as well as quantitative research with a self-administered survey that conveniently samples consumers who have previously engaged in a hair transplant or liposuction in USA and India. This research introduces a method that pinpoints and maps out anticipated positive and negative emotions in hedonic adaptation to repeated consumption. It implements an empirical framework that explains and predicts decision-making in hedonic consumption.